Evaluation of increased high-sensitivity cardiac troponin in patients with radiofrequency ablation - İçen, Yahya Kemal and Koç, Mevlüt (Journal of Surgery and Medicine, 2018)
Aim: In our study; we explored which ablation parameter is mostly associated with the increased high-sensitivity troponin tests (hs-cTnT) in patients undergone radiofrequency ablation (RFA). Methods: We included patients who underwent RFA within the previous year, and later admitted to emergency service with chest pain to our study. ECG and echocardiographic examination were performed before the electrophysiological study (EPS) for all patients. After RFA, information regarding the total duration, energy and mean temperature was recorded. Blood samples were collected via venous route from patients who underwent RFA, and later admitted to emergency service with chest pain to study hs-cTnT. Results: There were 119 patients [38 males, median age 51years (IQR:29)] included in our study. 6 of them (80.7%) were detected to have atrioventricular nodal re-entrant tachycardia (AVNRT), 14(11.8%) Wolff Parkinson White Syndrome (WPW), and 9 (7.5%) Right Ventricular Outflow Tract (RVOT) Tachycardia. Hs-cTnT and total RFA duration (r=0.683,p<0.001), total energy (r=0.423, p<0.001) and mean temperature (r=0.371, p<0.001) were correlated. In linear regression analysis; total RFA duration (OR:0.842, 95% CI: 0.685-0.999, p<0.001) and mean temperature (OR:10.738, 95% CI: 6.420-15.055, p<0.001) were detected to be independent predictors for hs-cTnT. Conclusion: This study has shown us that it should be noted that patients who underwent RFA for a prolonged duration and at high temperature may admit to the emergency service with chest pain, therefore, their troponin levels may increase, and also in these patients no further work-up or treatment would be required.